Comprehensive Analysis of The Concept of Business Crime and its Derivatives: White-Collar Crime, Fraud, Corruption, and Money Laundering - Yudhanta Sambharakreshna (Journal of Business Crime, 2025)
Objective: This report aims to provide a comprehensive understanding of the theory and concepts of business crime and its derivatives, including definitions, characteristics, motivating theories, types, impacts, and relevant legal frameworks in Indonesia.Research Design & Methods: This study adopts a qualitative approach using desk research methods. Data was collected from various secondary sources, including scientific journals, laws, official government reports, and academic publications. The information collected was then analyzed descriptively to identify definitions, characteristics, theories, impacts, and applicable legal frameworks.Findings: Research shows that business crimes, including white-collar crime, fraud, corruption, and money laundering, have massive financial, economic, and social impacts. The legal framework in Indonesia has been strengthened, particularly with the recognition of corporate criminal liability in the New Criminal Code (Law No. 1 of 2023) and the crucial role of institutions such as the Financial Transaction Reports and Analysis Center (PPATK) and the Financial Services Authority (OJK) in combating money laundering. Implications and Recommendations: Theoretically, this study highlights the need for a more sophisticated criminological framework to explain crimes committed by high-status individuals. Practically, this report highlights significant challenges in law enforcement, such as the difficulty of identifying corporate perpetrators, asset tracing, and the importance of law enforcement integrity and public trust. Contribution and Value Added: This report contributes by offering concrete recommendations for strengthening the legal framework, improving law enforcement capacity, internal and external oversight, building a culture of integrity, public education, and international cooperation to effectively prevent and combat business crime